2016
DOI: 10.11591/ijeecs.v1.i3.pp456-463
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Solar Panel Performance Based on Different Wind Velocity Using ANSYS Software

Abstract: <p> The low conversion energy efficiency of solar panel is affected by the several environmental issues. Solar radiation, ambient temperature, dust accumulation and wind velocity are the environmental problems. This main goal of this paper is to understanding the solar panel behavior under varying of wind velocity amounts. A three-dimension (3-D) model of solar panel is conducted in the present investigation. The solar panel model is simulated under given operating condition and different amounts of wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Leow et al (2016) analyzed the effect of wind speed on the temperature distribution of solar panels. Their study highlighted how increased wind speeds could moderate panel temperatures effectively, yet failed to consider the variations in panel inclination angles which could significantly alter these effects [18].…”
Section: Introductionmentioning
confidence: 99%
“…Leow et al (2016) analyzed the effect of wind speed on the temperature distribution of solar panels. Their study highlighted how increased wind speeds could moderate panel temperatures effectively, yet failed to consider the variations in panel inclination angles which could significantly alter these effects [18].…”
Section: Introductionmentioning
confidence: 99%
“…While [24] reported that the amount of electrical power generated using photovoltaic modules depends on the temperature of the cells; the higher the cell temperature, the higher the lost in power output. [25] revealed that to obtain better performance efficiency from photovoltaics they should be operated in an environment with considerable wind speed to enable adequate cooling of the PV modules. While [26] employed multi-concept cooling techniques to enhance the output power and efficiency of PV modules.…”
Section: Introductionmentioning
confidence: 99%
“…The PV module performance has been represented by several models aimed at increasing system power output. Various authors have modelled the critical PV module temperature and its relation to meteorological conditions [22][23][24][25][26][27][28][29][30], primarily through considering thermal radiation, convection, and conduction mechanisms relating to the power generated. For example, Armstrong et al [31] studied an overall thermal response as a function of loss coefficient, resulting in a linear relationship between module temperature and irradiance under steady-state conditions.…”
Section: Introductionmentioning
confidence: 99%